Cardiovascular Complications of Down Syndrome: Scoping Review and Expert Consensus. Issue 5 (31st January 2023) - Dimopoulos, Konstantinos; Constantine, Andrew; Clift, Paul; Condliffe, Robin; Moledina, Shahin; Jansen, Katrijn; Inuzuka, Ryo; Veldtman, Gruschen R.; Cua, Clifford L.; Tay, Edgar Lik Wui; Opotowsky, Alexander R.; Giannakoulas, George; et al.
Abstract : Cardiovascular disease is a leading cause of morbidity and mortality in individuals with Down syndrome. Congenital heart disease is the most common cardiovascular condition in this group, present in up to 50% of people with Down syndrome and contributing to poor outcomes. Additional factors contributing to cardiovascular outcomes include pulmonary hypertension; coexistent pulmonary, endocrine, and metabolic diseases; and risk factors for atherosclerotic disease. Moreover, disparities in the cardiovascular care of people with Down syndrome compared with the general population, which vary across different geographies and health care systems, further contribute to cardiovascular mortality; this issue is often overlooked by the wider medical community. This review focuses on the diagnosis, prevalence, and management of cardiovascular disease encountered in people with Down syndrome and summarizes available evidence in 10 key areas relating to Down syndrome and cardiac disease, from prenatal diagnosis to disparities in care in areas of differing resource availability. All specialists and nonspecialist clinicians providing care for people with Down syndrome should be aware of best clinical practice in all aspects of care of this distinct population.